Development of an ISO 55000 compliant central management framework for asset care plans within a multi-technology portfolio of renewable energy power plants in the South African energy sector - Saunders, Compton Colin (Stellenbosch : Stellenbosch University, 2016)
Thesis (MEng)--Stellenbosch University, 2016.